The Ritual Tradition of Rejecting Reinforcements Preserves Sacred Art Values in the Kuantan Singingi Community, Riau Province - Narulita, Fina; Budiwirman, Budiwirman; Daryusti, Daryusti; Erianjoni, Erianjoni (LANGGAM: International Journal of Social Science Education, Art and Culture, 2025)
This study aims to analyze the Ritual Tradition of Rejecting Evil, which carries sacred art values within the Kuantan Singingi community in Riau Province. The research employs a descriptive qualitative method with an analytical approach and literature review. The art criticism theory used refers to four key aspects: description, formal analysis, interpretation, and evaluation. Feldman’s art criticism theory is chosen for its ability to provide a deeper and more objective analysis of the subject matter, particularly the krumpyung music. Data collection was carried out through observations, in-depth interviews with traditional leaders and community members regarding the ritual, and written documentation. Data reliability was ensured through source triangulation, and data analysis followed a four-stage process: data collection, data reduction, data presentation, and conclusion. The findings reveal that the Ritual Tradition of Rejecting Evil in the Kuantan Singingi community is rooted in animistic and dynamistic beliefs, practices that predate the arrival of Islam. Living in close connection with nature, and with limited technological resources, the community has long sought to maintain a harmonious relationship with their environment, which they believe is inhabited or controlled by spiritual beings. The sacred art values embedded in the ritual remain alive, with the Petalangan community continuing to perform the ritual annually. Despite exposure to various other cultures, this tradition endures due to several factors: the inheritance of tradition, its role in disaster protection, and its ability to foster social solidarity within the community. In conclusion, the Ritual of Rejecting Evil is not just a cultural tradition but a living expression of spiritual values that continue to shape the community's identity. This study hopes to serve as a reference for further research into similar traditions and sacred art values in other indigenous communities.